The Dedication: Leaving Evidence of Life, Death, Care, and Confinement During COVID-19 - Hailee M. Yoshizaki-Gibbons (Lateral, 2023)
In 2020, the COVID-19 pandemic exploded and nursing homes rapidly became overwhelmed with disease, death, and despair. During this time, I learned Sylvia, an old woman with dementia I had befriended, was one of the many old and disabled people confined in nursing homes who did not survive. In this reflective and part personal, part scholarly essay, I leave evidence of and for Sylvia and the nearly 200,000 old and disabled people and care workers who contracted COVID-19 and died within the confines of neoliberal, profit-driven long-term care institutions. Disability justice activist Mia Mingus writes, “We must leave evidence. Evidence that we were here, that we existed, that we survived and loved and ached.” Leaving evidence is a political act, a form of resistance in an ableist word. And yet leaving evidence is particularly challenging in the context of dementia, care, confinement, and death—making it even more important, more urgent. Building on Ellen Samuels’ assertion, “Crip time is grief time,” I consider how mourning Sylvia and countless other nursing home deaths, interwoven with my own experiences of distress, yet also solidified my need to survive, might leave evidence and keep working toward an abolitionist future—one in which old and disabled women like Sylvia, like my future self, might thrive.